THE INFLUENCE OF SALES PROMOTION AND STORE ATMOSPHERE TOWARDS IMPULSE BUYING WITH SHOPPING EMOTION AS INTERVENING VARIABLE - ASRINTA, PRASASTI SEKAR (JOURNAL OF RESEARCH IN MANAGEMENT, 2018)
The purpose of this research is to know and analyze the influence of sales promotion andstore atmosphere toward customers shopping emotion, sales promotion, store atmosphere,and shopping emotion toward customers impulse buying, and the influence of salespromotion and store atmosphere toward impulse buying with shopping emotion asintervening variable. The sample in this study there are 125 respondents who areconsumers of Matahari Department Store Purwokerto. Convenience sampling method isused in the determination of this research sample. Data were analyzed using StructuralEquational Modeling (SEM) with SPSS and AMOS statistical software.The results of thisstudy show that, sales promotion and store atmosphere have positive influence on shoppingemotion and impulse buying. Thus, sales promotion and store atmosphere have positiveinfluence on impulse buying with emotion as intervening variable at customers of MatahariDepartment Store Purwokerto.